2021
DOI: 10.1093/jamia/ocab216
|View full text |Cite
|
Sign up to set email alerts
|

Spanish adaptation and validation of the User Version of the Mobile Application Rating Scale (uMARS)

Abstract: Objective While the professional version of the Mobile App Rating Scale (MARS) has already been translated, and validated into the Spanish language, its user-centered counterpart has not yet been adapted. Furthermore, no other similar tools exist in the Spanish language. The aim of this paper is to adapt and validate User Version of the MARS (uMARS) into the Spanish language. Materials and Methods Cross-cultural adaptation, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…The results of this review reflect the value of eHealth from the perspective of users, who are important sources of practical implications for the development and implementation of eHealth [ 87 , 88 ]. Our results showed that users place a high value on an eHealth technology that offers accurate diagnoses of health problems, has interactive features, and facilitates real-time communication with health professionals [ 89 - 91 ].…”
Section: Discussionmentioning
confidence: 96%
“…The results of this review reflect the value of eHealth from the perspective of users, who are important sources of practical implications for the development and implementation of eHealth [ 87 , 88 ]. Our results showed that users place a high value on an eHealth technology that offers accurate diagnoses of health problems, has interactive features, and facilitates real-time communication with health professionals [ 89 - 91 ].…”
Section: Discussionmentioning
confidence: 96%
“…22 This study illustrates that the linguistic validation of the Greek uMARS is consistent with the cross-sectional validations of other languages. 12,[23][24][25] At present, the Greek version of the uMARS is being tested by end users to evaluate the medical app that prompted this project.…”
Section: Discussionmentioning
confidence: 99%
“…We will use the Spanish Version of the User Version of the Mobile Application Rating Scale (uMARS) ( 57 ), that will serve as a comprehensive and objective measure of app usability, consisting of 20 items. Each item is assessed using a 5-point scale, ranging from 1 (inadequate) to 5 (excellent).…”
Section: Methods and Analysismentioning
confidence: 99%